Analisis Teologi Kontekstual: Relevansi Doktrin Dosa Asal Agustinus dan Ritual Dara Ta’a di Desa Loce, Kecamatan Reok Barat, Manggarai - Herman A.T. Sekosi; Leo Esandri Narong; Marianus Gajak Maran (STT Pelita Dunia, 2026)
Through this study, the author demonstrates that Christian theology is not merely a theoretical concept but is also relevant to local culture, capable of enriching the meaning of faith in people’s lives. This study aims to examine the relevance of Augustine’s doctrine of original sin to the ritual practice of Dara Ta’a—often referred to as Dara Lampek—in Manggarai culture, specifically in the village of Loce. This study employs a descriptive-analytical qualitative method through a literature review drawing on theological and anthropological sources. The primary source for this study is Augustine’s doctrine of original sin, which addresses the inherited sin of Adam, while secondary sources were obtained from various anthropological studies published in journals that discuss the Dara Ta’a ritual in Manggarai culture. The analysis was conducted using a contextual theological approach that seeks to understand and reflect on the theology of original sin in dialogue with the cultural context of Manggarai. The novelty of this article lies in the research findings, which show that both the doctrine of original sin and the Dara Ta’a ritual embody an awareness of sin and the importance of restoring relationships. Augustine’s theology of original sin and the Dara Ta’a ritual can be understood as expressions of humanity’s longing for restoration and salvation. Therefore, this article is intended to help foster a dialogue between theology and local culture in order to revitalize faith so that it remains rooted in the context of real life.